2020
DOI: 10.1002/ijfe.1862
|View full text |Cite
|
Sign up to set email alerts
|

What drives the duration of credit booms?

Abstract: This paper presents a new perspective on the study of credit booms by both examining what determines their duration and testing for relevant political features. The results from the estimation of a discrete‐time duration model show that both the economic and the political environment influence the duration of credit booms. These events are found to last longer when: (a) the economy is growing faster; (b) levels of liquidity in the banking system are lower; (c) current account position deteriorates; (d) centre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, in their study, Castro and Martins (2020) do find that credit expansions that end in banking crisis (the so‐called 'bad' credit booms) are more prone to last longer than those that end softly. This also leads to the question of whether there is a difference in the role of FFC in these two types of booms.…”
Section: Literature and Hypothesesmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, in their study, Castro and Martins (2020) do find that credit expansions that end in banking crisis (the so‐called 'bad' credit booms) are more prone to last longer than those that end softly. This also leads to the question of whether there is a difference in the role of FFC in these two types of booms.…”
Section: Literature and Hypothesesmentioning
confidence: 96%
“…Moreover, they find that while credit booms in emerging countries are often preceded by foreign capital inflows, booms in developed economies are preceded by productivity gains or financial reforms. On the other hand, by deploying a duration model, Castro and Martins (2020) find no evidence for credit booms lasting longer in non‐OECD countries versus those in OECD countries. To investigate whether the role of FFC differs for emerging versus developed economies, in this study, I consider both types of countries separately.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…Bad credit booms, that is, those associated with financial crises, occur in the context of high inflation and low economic growth (Barajas et al, 2009). Furthermore, it has been observed that the determinants of the duration of credit booms (Castro & Martins, 2021a) are primarily related to economic (fast economic growth, bank liquidity, deterioration of current accounts) and political factors (the presence of center parties in office and government coalitions).…”
Section: Determinants Of Credit Boomsmentioning
confidence: 99%